A light addressable electrode with a TiO2 nanocrystalline film for localized electrical stimulation of cultured neurons - Suzurikawa, Jun; Nakao, Masayuki; Jimbo, Yasuhiko; Kanzaki, Ryohei; Takahashi, Hirokazu (Sensors and actuators. B, Chemical, 2014)
To improve the existing light-addressable electrode (LAE) for neuronal stimulation, we attempted to replace a photoconductive layer of hydrogenated amorphous silicon (a-Si:H), which is subject to corrosion in cell culture environments, with a TiO2 nanocrystalline film. As seen in previous LAEs with a-Si:H, the TiO2 film formed on a metal film electrode serves as a photo-switch: UV light illumination locally increases the conductivity of the TiO2 film and generates a virtual electrode. TiO2 is a lower cost material, easier to fabricate than a-Si:H, and more compatible with cell culture environments; thus, it does not require a passivation layer on top. The measurements of photoelectric characteristics of TiO2 LAE ascertained that adequate photo-switching properties for selective neuronal stimulation were achieved; however, two possible issues that could affect performance were identified: degradation of the photo-switching property due to electrolyte penetration into the TiO2 film and a slow switching response due to charge carrier trapping into surface defects. Despite these issues, however, the feasibility of light-addressed electrical stimulation with the proposed TiO2 LAE was successfully demonstrated in an experiment using a primary neuron-glia co-culture. Thus, TiO2 is an alternative candidate to a-Si:H in photo-electrochemical biointerfaces.